Developing a structural model of the relationship between early maladaptive schemas and emotion regulation with the mediating role of psychological hardiness in people with anxiety disorders - Fatemeh Ariyansepehr; Leila Moghtader; Bahman Akbari Govaberi (مجله علوم روانشناختی, 2024)
Background: One of the deep cognitive processes that play a fundamental role in the development of anxiety disorders is early maladaptive schemas. Another underlying cause of anxiety disorders is the inability to emotion regulation. Also, psychological hardiness as an important personality structure is effective on the way and quality of dealing with Sources of anxiety. So far, no specific research has focused on presenting a structural model regarding the relationship between primary maladaptive schemas and emotional regulation with the mediating role of psychological hardiness in patients with anxiety disorders. Aims: The present study was conducted with the aim of developing a structural model of the relationship between early maladaptive schemas and emotion regulation with the mediating role of psychological hardiness. Methods: The design of the current research was descriptive and correlational. The statistical population of this research included all people suffering from anxiety disorders who referred to counseling centers and psychological services under the supervision of Tehran Welfare Organization in 2022. Using the random multistage cluster sampling method, 300 people with anxiety disorders were selected as the statistical sample of the research. To collect information from the questionnaires of the short version of the Early Maladaptive Schema -Short Form (Young, 1998); Emotion regulation strategies (Gross & John, 2003) and Psychological hardiness (Kobasa, 1979) were used. To analyze the data in this study, correlation and path analysis methods were used using SPSS-26 and AMOS-24 software. Results: The findings of the present study showed that the proposed model has a good fit.The results also show that the schemas of disconnection and rejection, Impaired autonomy and Performance, orientation, over-vigilance and inhibition had a negative and significant effect on emotional reappraisal and a positive and significant effect on emotional suppression. Also, the effect of Impaired Limits schema on suppression was positive and significant. Psychological hardiness has a positive and significant effect on emotional reappraisal and a negative and significant effect on emotional suppression. Conclusion: According to the results obtained, the mediating role of the psychological hardiness variable was confirmed in the present study, And since this variable increases a person's resilience and as a result puts her in a positive and healthy cycle, it is suggested that counseling centers therapists teach people with anxiety disorders techniques to improve psychological hardiness.